Effects of dietary supplementation with different levels of rose pomace on rumen bacterial diversity and fermentation, and longissimus dorsi fatty acids in Hu sheep - Linjiao He; Linjiao He; Linjiao He; Ruirui Tian; Ruirui Tian; Ruirui Tian; Ziting Wang; Ziting Wang; Ziting Wang; Jinlong Li; Jinlong Li; Jinlong Li; et al. (Frontiers in Microbiology)
To address the underutilization of rose processing byproducts and meet the demand for antibiotic-free meat production, this study examined the effects of dietary supplementation with rose pomace (RP) on growth performance, rumen fermentation, bacterial diversity, and longissimus dorsi amino acid and fatty acid profiles in Hu sheep. Forty male Hu sheep were randomly assigned to four groups (n = 10): a control group (RP0) with a basal diet and three treatment groups supplemented with 2, 4, or 8% RP (RP2, RP4, RP8). Results showed that RP8 had significantly higher dry matter intake (DMI) than RP2 (P ≤ 0.05). Rumen fermentation analysis indicated higher acetate in RP4 than RP0 (P ≤ 0.05), while propionate and total volatile fatty acids (TVFA) were lower in RP0 than in all RP groups (P ≤ 0.05). RP8 exhibited significantly elevated isobutyrate (P ≤ 0.05) and isovalerate (P ≤ 0.01), with valerate levels higher in RP4 and RP8 than RP0 (P ≤ 0.05). Microbial analysis revealed increased Bacteroidota and reduced Patescibacteria in RP8 (P ≤ 0.05). RP8 also showed higher Rikenellaceae_RC9_gut_group abundance (P ≤ 0.05). In longissimus dorsi muscle, RP4 had significantly higher C18:3N3, N-3 PUFAs, and C20:2N6 than RP0 and RP8 (P ≤ 0.05). These findings suggest RP modulates rumen microbiota and fermentation, enhancing beneficial fatty acid deposition in lamb meat. An RP supplementation level of 2–4% yielded optimal results, providing valuable insights for sheep farmers seeking functional feed additives.